Sharia Retail Store Service Standards Based on Customer Preferences in the Cooperative Ecosystem - Hakim, Abdurrahman; Suryadi, Nanang; Huda, Choirul (Universitas Brawijaya, Indonesia, 2024)
Cooperative-based Islamic retail businesses need to measure and improve their service performance to increase customer satisfaction to be superior in competitive markets. The adaptation of the SERVQUAL (service quality) measurement to the RSQS (retail service quality scale) scale has no sharia and co-operative dimensions. Therefore, the RSQS scale needs to be adapted to be SC-RSQS (Sharia_Co-operative_Retail Service Quality Scale) with the addition of sharia and cooperative dimensions. This adaptation has been validated by the panel of experts. On the other hand, SERVPERF (service performance) serves as a solution to the SERVQUAL weaknesses in measuring service performance. Satisfaction- and dissatisfaction-causing factors can be classified using Kano's Model. Records of consumer desires are needed to qualitatively fill deeper substances, which are analyzed using coding analysis. The integration of SC-RSQS in SERVPERF and Kano's Model was emphasized in this paper and was clarified using the coding analysis of customer records. This paper aimed to measure service performance, categorize customer requirements, and identify things that need to be considered in improving the performance of the 212 Mart cooperative retail store service in South Jakarta, Indonesia. The results show the level of satisfaction of cooperative members as the main consumers of this business is lower than non-cooperative members, 87% of customer requirements are in one-dimensional category, and the potential for customer dissatisfaction is higher than the potential satisfaction. 212 Mart must give cooperative members greater benefits than non-cooperative members, be more sensitive in providing services, and try to be more communicative with customers, especially cooperative members.